Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Three new prenylated phoroglucinols from Hypericum henryi with anti-neuroinflammatory activities - Chang-Hao Luo; Mi Yang; Ming-Gen Tang; Jing-Yu Luo; Jia-Yi Qu; Chang-Wang Luo; Ye-Juan An (Phytochemistry Letters, 2026)

Transgene-free genome editing in citrus and poplar meristem tissues via biolistic ribonucleoprotein delivery of CRISPR-Cas9 - Dhiôvanna Corrêia Rocha; Miracle Osazee Omoregbee; Weifeng Luo; Hong Fang; Qiushi Ye; Yanxin Liu; Gen Li; Juliet Mascoveto; Alessandra Alves de Souza; Gary Coleman; James N. Culver; Yiping Qi (Plant Cell Reports, 2026)
Key message Biolistic particle bombardment was used to deliver CRISPR-Cas9 ribonucleoprotein complexes (RNP) into the shoot apical meristem tissue of citrus and axillary meristem tissue of poplar, generating directed mutations in target genes. Abstract The use of meristematic tissues offers a strategic approach to genome editing in woody species, especially those that are recalcitrant to conventional tissue culture, as these regions contain totipotent, highly regenerative cells capable of giving rise to whole plants. Here, we employed biolistic delivery of genome-editing reagents into theshoot apical meristem (SAM) of citrus and the axillary meristems (AXM) of poplar. The system was first validated using a GFP expression construct and subsequently applied for targeted genome editing. In citrus, edited plants were obtained at the CsNPR3 locus exclusively through the delivery of CRISPR/Cas9 ribonucleoproteins (RNPs), whereas plasmid-based vectors were unsuccessful. Similarly, genome editing in poplar was achieved using RNPs targeting the Pt4CL1 gene. Although chimeric events were detected, this approach provides a feasible and innovative framework for producing transgene-free edited perennial plants.

Effects of dietary manganese chelate (Mn-MHA) on growth, muscle characteristics and antioxidant capacity and inflammatory response of largemouth bass (Micropterus salmoides) - Chong-Chao Zhong; Chang-Chun Song; Yannis P. Kotzamanis; Hong Yang; An-Gen Yu; Hua Zheng; Zhi Luo (Aquaculture, 2026)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Newly discovered cyanobacteria Nostoc sp. PCC7120 for high efficiency biodegradation of thiamethoxam: Photosynthesis response, enzyme strategies, and molecular mechanisms - Shiye Zhu; Jiale Zhang; Anwei Chen; Youzheng Chai; Jianhua Zeng; Gen Lu; Ma Bai; Jihai Shao; Liang Peng; Si Luo (Bioresource Technology, 2025)

Damage evolution characteristics of the shear band-bedrock interface under dry-wet cycling: experimental and numerical simulation - Xueyan Guo; Suliman Lojain; Xinrong Liu; Xinyang Luo; Fuchuan Zhou; Hao Wang; Gen Wang (Journal of Mountain Science, 2025)

SAR imaging simulation of ship wake on the finite depth sea surface - Gen Luo; Zhi-Hua Xiong; Ming-Bin Zhou; Jia Zhang; Qi-Xin Wan (International Journal of Remote Sensing, 2025)

Evolutionary dynamics and codon bias analysis of canine circovirus: Insights into global spread and host adaptability - Gen Li; Rongqi Liu; Yongyi Chen; Huixian Liang; Yinyi Liang; Xin Li; Yankun Ke; Bowen Lin; Jianfeng Zhong; Xiaofeng Guo; Jun Che; Jun Luo (Molecular Phylogenetics and Evolution, 2025)

Porcine epidemic diarrhea virus induces mitophagy to inhibit the apoptosis and activation of JAK/STAT1 pathway - Xin Li; Yiwan Wu; Jin Peng; Bingjie Li; XiaoLong Li; Zhibin Yan; Gen Li; Yue Zhang; HongLing He; Jun Luo; Xiaofeng Guo (Veterinary Microbiology, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Short-term exposure of enrofloxacin inhibits synthesis of central estradiol through secretoneurin a/aromatase B (cyp19a1b) pathway in crucian carp - Huazhong Liu; Gen Wan; Ping Luo; Jianzhen Huang; Jiayi Wu; Zhuocheng Nie; Jiming Ruan (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Interaction between dietary zinc (Zn) and manganese (Mn) on growth performance, intestinal health and lipid metabolism in yellow catfish - Wu-Hong Lv; Fan Wu; Mette Sorensen; Xiao-Ying Tan; Xiao-Lei Wei; An-Gen Yu; Chong-Chao Zhong; Yu-Feng Song; Zhi Luo (Aquaculture, 2025)

Predicting wheat scab levels based on rotation detector and Swin classifier - Dongyan Zhang; Zhipeng Chen; Hansen Luo; Gensheng Hu; Xin-Gen Zhou; Chunyan Gu; Liping Li; Wei Guo (Biosystems Engineering, 2024)

Deciphering the biodegradation of thiamethoxam by Phanerochaete chrysosporium with natural siderite: Synergistic mechanisms, transcriptomics characterization, and molecular simulation - Shiye Zhu; Anwei Chen; Jiale Zhang; Si Luo; Jizhao Yang; Youzheng Chai; Jianhua Zeng; Ma Bai; Zhenghang Yang; Gen Lu (Journal of Hazardous Materials, 2024)

Correction: A New Safety Control Method of Blasting Excavation in High Rock Slope with Joints - Yingguo Hu; Zhaowei Yang; Shuling Huang; Wenbo Lu; Gen Zhao; Cong Luo (Rock Mechanics and Rock Engineering, 2024)

Peteryoungia algae sp. nov. isolated from seaweeds of Gouqi Island, China, and its unique genetic features among Peteryoungia strains - Jun Yin; Min He; Xiao-Xiao Liu; Chang-Bin Ren; Hou-Hong Liu; Hai Luo; Gen Chen; Ze-Fei Wang; Sanjit Chandra Debnath; Pin-Mei Wang; Hai-Xin Chen; Dao-Qiong Zheng (Antonie van Leeuwenhoek, 2024)

Catalytically ultrathin titania coating to enhance energy storage and release of aluminum hydride via atomic layer deposition - Zhijia Hu; Xingxing Xu; Huachen Shao; Ruidong Luo; Mingxuan Wang; Gen Tang; Xiao Liu; Bin Shan; Rong Chen (Chemical Engineering Journal, 2024)

Characterization and Genomic Analysis of Affinirhizobium gouqiense sp. nov. Isolated from Seawater of Gouqi Island Located in the East China Sea and Reclassification of Rhizobium lemnae to the Genus Affinirhizobium as Affinirhizobium lemnae comb. nov. - Min He; Gen Chen; Ke-Jing Li; Xing-Xing Tang; Xiao-Xiao Liu; Chang-Bin Ren; Hou-Hong Liu; Hai Luo; Sanjit Chandra Debnath; Pin-Mei Wang; Hai-Xin Chen; Dao-Qiong Zheng (Current Microbiology, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Severe photochemical pollution formation associated with strong HONO emissions from dew and guttation evaporation - Wanyun Xu; Ye Kuang; Chang Liu; Zhiqiang Ma; Xiaoyi Zhang; Miaomiao Zhai; Gen Zhang; Weiqi Xu; Hongbing Cheng; Yusi Liu; Biao Xue; Biao Luo; et al. (Science of The Total Environment, 2024)

Limonoids from the roots of Melia azedarach and their anti-inflammatory activity - Min Song; Hui-Juan Luo; Zi-Wei Li; Ling Qiu; Yu-Xin Zhao; Cheng-Wei He; Xiao-Qi Zhang; Wen-Cai Ye; Li-Gen Lin; Qing-Wen Zhang (Phytochemistry, 2023)

High-performance Cu/Mn modified ceramsite as a persulfate activator to degrade oxytetracycline in batch Erlenmeyer flask and continuous-flow fixed-bed column systems: An exploration of its practicability and non-radical mechanisms - Huang-gen Yang; Mang Lu; Xue-jiao Wu; Rui-ting Dong; Tao-peng Luo; Hui-hua Zhong (Chemosphere, 2023)

Enhancing wheat Fusarium head blight detection using rotation Yolo wheat detection network and simple spatial attention network - Dong-Yan Zhang; Han-Sen Luo; Tao Cheng; Wei-Feng Li; Xin-Gen Zhou; Wei-Guo; Chun-Yan Gu; Zhihua Diao (Computers and Electronics in Agriculture, 2023)

New evidence of the Hoyle-like structure in 16O - Jiahao Chen; Yanlin Ye; Kai Ma; Jiaxing Han; Dongxi Wang; Chengjian Lin; Huiming Jia; Lei Yang; Gen Li; Lisheng Yang; Ziyao Hu; Zhiwei Tan; et al. (Science Bulletin, 2023)

Noninvasive Tracking of Every Individual in Unmarked Mouse Groups Using Multi-Camera Fusion and Deep Learning - Feng Su; Yangzhen Wang; Mengping Wei; Chong Wang; Shaoli Wang; Lei Yang; Jianmin Li; Peijiang Yuan; Dong-Gen Luo; Chen Zhang (Neuroscience Bulletin, 2023)

Petrogenesis of the Late Cretaceous Sillai Patti carbonatites, NW Pakistan: Insights from C-O-Sr-Nd isotopes and titanite U Pb dating - Yu-Xiang Zhu; Lian-Xun Wang; Nimat Ullah Khattak; Chang-Qian Ma; Gen-Ming Luo; Thomas Ulrich (Lithos, 2023)

46,XY disorders of sex development: the use of NGS for prevalent variants - Qi-Gen Xie; Peng Luo; Kai Xia; Zuo-Qing Li; Zhe Xu; Cheng Su; Chun-Hua Deng (Human Genetics, 2022)

Correction to: Preliminary analyses of the Tiejiangwan landslide occurred on April 5, 2021 in Hongya County, Sichuan Province, China - Bo Liu; Xiewen Hu; Kun He; Gen Li; Xin Liu; Gang Luo; Chuanjie Xi; Ruichen Zhou (Landslides, 2022)

Preliminary analyses of the Tiejiangwan landslide occurred on April 5, 2021 in Hongya County, Sichuan Province, China - Bo Liu; Xiewen Hu; Kun He; Gen Li; Xin Liu; Gang Luo; Chuanjie Xi; Ruichen Zhou (Landslides, 2022)

Carbon storage of the forest and its spatial pattern in Tibet, China - Long-yu Jia; Gen-xu Wang; Ji Luo; Fei Ran; Wei Li; Jun Zhou; Dan-li Yang; Wen-bo Shi; Qian Xu; Kun Zhu; Yang Yang (Journal of Mountain Science, 2021)

METTL1 overexpression is correlated with poor prognosis and promotes hepatocellular carcinoma via PTEN - Qiu-Hong Tian; Mei-Fang Zhang; Jin-Sheng Zeng; Rong-Guang Luo; Yang Wen; Jun Chen; Liu-Gen Gan; Jian-Ping Xiong (Journal of Molecular Medicine, 2019)

Early diagnosis of acute kidney injury in aged patients undergoing percutaneous coronary intervention - Hong-hua Ye; Gen Shen; Qun Luo; Fang-fang Zhou; Xiao-ling Xie; Chun-yan Wang; Li-na Han (Journal of Zhejiang University-SCIENCE B, 2018)

Protective effects of paeonol on inflammatory response in IL-1β-induced human fibroblast-like synoviocytes and rheumatoid arthritis progression via modulating NF-κB pathway - Ke-feng Zhai; Hong Duan; Lin Luo; Wen-gen Cao; Fang-kai Han; Ling-ling Shan; Xue-mei Fang (Inflammopharmacology, 2017)

Allometric equations of select tree species of the Tibetan Plateau, China - Fei Ran; Rui-ying Chang; Yang Yang; Wan-ze Zhu; Ji Luo; Gen-xu Wang (Journal of Mountain Science, 2017)

Ground bryophytes regulate net soil carbon efflux: evidence from two subalpine ecosystems on the east edge of the Tibet Plateau - Shou-Qin Sun; Tao Liu; Yan-Hong Wu; Gen-Xu Wang; Bo Zhu; Thomas Henry DeLuca; Yan-Qiang Wang; Ji Luo (Plant and Soil, 2017)

Puerarin-7-O-glucuronide, a water-soluble puerarin metabolite, prevents angiotensin II-induced cardiomyocyte hypertrophy by reducing oxidative stress - Ning Hou; Bin Cai; Cai-Wen Ou; Zhen-Hui Zhang; Xia-Wen Liu; Mu Yuan; Gan-Jian Zhao; Shi-Ming Liu; Long-Gen Xiong; Jian-Dong Luo; Cheng-Feng Luo; Min-Sheng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

The combination of osthole with baicalin protects mice from Staphylococcus aureus pneumonia - Shui Liu; Bowen Liu; Zhao-Qing Luo; Jiaming Qiu; Xuan Zhou; Gen Li; Bing Zhang; Xuming Deng; Zhenguo Yang; Jianfeng Wang (World Journal of Microbiology and Biotechnology, 2017)

Effects of excessive equatorial cold tongue bias on the projections of tropical Pacific climate change. Part I: the warming pattern in CMIP5 multi-model ensemble - Gen Li; Shang-Ping Xie; Yan Du; Yiyong Luo (Climate Dynamics, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Heat stress impairs mice granulosa cell function by diminishing steroids production and inducing apoptosis - Man Luo; Lian Li; Cheng Xiao; Yu Sun; Gen-Lin Wang (Molecular and Cellular Biochemistry, 2016)

Nitrate facilitates cadmium uptake, transport and accumulation in the hyperaccumulator Sedum plumbizincicola - Pengjie Hu; Yong-Gen Yin; Satoru Ishikawa; Nobuo Suzui; Naoki Kawachi; Shu Fujimaki; Masato Igura; Cheng Yuan; Jiexue Huang; Zhu Li; Tomoyuki Makino; Yongming Luo; et al. (Environmental Science and Pollution Research, 2013)

Erratum to: UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

UDP-glucuronosyltransferase 1A1 is the principal enzyme responsible for puerarin metabolism in human liver microsomes - Cheng-Feng Luo; Bin Cai; Ning Hou; Mu Yuan; Shi-Ming Liu; Hong Ji; Long-Gen Xiong; Wei Xiong; Jian-Dong Luo; Min-Sheng Chen (Archives of Toxicology, 2012)

A new plastic surgical technique for adult congenital webbed penis - Yue-bing Chen; Xian-fan Ding; Chong Luo; Shi-cheng Yu; Yan-lan YU; Bi-de Chen; Zhi-gen Zhang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2012)

The Prevalence of Type 2 Diabetes and Hypertension in Uygur and Kazak Populations - Yicun Tao; Xinmin Mao; Zijing Xie; Xinjian Ran; Xiaoyan Liu; Ye Wang; Xin Luo; Mengying Hu; Wenning Gen; Minfang Zhang; Tao Wang; Jun Ren; et al. (Cardiovascular Toxicology, 2008)

Antifungal compounds from Bacillus subtilis B-FS06 inhibiting the growth of Aspergillus flavus - Ting Zhang; Zhi-Qi Shi; Liang-Bin Hu; Luo-Gen Cheng; Fei Wang (World Journal of Microbiology and Biotechnology, 2008)